Protein levels of CC chemokine ligand (CCL)15, CCL16 and macrophage stimulating protein in patients with sarcoidosis - Arakelyan, A; Kriegova, E; Kubistova, Z; Mrazek, F; Kverka, M; du Bois, R M; Kolek, V; Petrek, M (Clinical and experimental immunology, 2009)
The objective of this study was to assess protein levels for candidate cytokines, chemokines, growth factors, matrix metalloproteinases and their inhibitors in bronchoalveolar lavage fluid (BALF) in patients with polar forms of pulmonary sarcoidosis, i.e. Löfgren's syndrome (LS) and more advanced chest X-ray (CXR) stage III disease. Twenty-four inflammatory molecules were analysed in unconcentrated BALF samples from 10 sarcoidosis patients with CXR stage III and 10 patients with LS by semiquantitative protein array. Four novel molecules [CC chemokine ligand (CCL)15, CCL16, macrophage migration inhibitory factor (MIF) and macrophage stimulating protein (MSP)], detected for the first time in association with sarcoidosis, were then quantified by enzyme-linked immunosorbent assay in a second cohort of 68 sarcoidosis patients and 17 control subjects. The protein levels of CCL15, CCL16, CCL24, CXCL8, CXCL9, CXCL10, interleukin-16, MIF, MSP and matrix metallopeptidase 1 were increased in CXR stage III patients when compared with patients with LS. CCL15 and MSP up-regulation in CXR stage III patients in comparison with LS patients and controls was confirmed by enzyme-linked immunosorbent assay. Moreover, MSP was associated with treatment requirement (P = 0.001) and CCL15 was elevated in patients with disease progression at 2-year follow-up (P = 0.016). CCL16 levels were increased in sarcoidosis versus controls (P < 0.05), but no difference was observed between patient subgroups. MIF up-regulation was not confirmed in a larger patient group. In conclusion, chemokines CCL15, CCL16 and MSP were found elevated for the first time in BALF from sarcoidosis patients; our results showed that CCL15 and MSP may affect disease course.
Keywords: Young Adult; Analysis of Variance; Macrophage Migration-Inhibitory Factors; Male; biologické markery; Inflammation; Up-Regulation; makrofágové zánětlivé proteiny; progrese nemoci; mladý dospělý; Biomarkers; plicní sarkoidóza; Proto-Oncogene Proteins; chemokiny CC; Adult; upregulace; Case-Control Studies; dospělí; imunohistochemie; mužské pohlaví; Disease Progression; Matrix Metalloproteinases; ELISA; zánět; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; studie případů a kontrol; analýza rozptylu; Immunohistochemistry; Humans; Sarcoidosis, Pulmonary; matrixové metaloproteinasy; Bronchoalveolar Lavage Fluid; Macrophage Inflammatory Proteins; Intramolecular Oxidoreductases; hepatocytární růstový faktor; bronchoalveolární lavážní tekutina; inhibiční faktory migrace makrofágů; Chemokines, CC; Female; lidé středního věku; intramolekulární oxidoreduktasy; protoonkogenní proteiny; Hepatocyte Growth Factor; Middle Aged